2019
DOI: 10.1103/physrevb.99.235135
|View full text |Cite
|
Sign up to set email alerts
|

Low offset frequency 1/f flicker noise in spin-torque vortex oscillators

Abstract: Low frequency noise close to the carrier remains little explored in spin torque nano oscillators. However, it is crucial to investigate as it limits the oscillator's frequency stability. This work addresses the low offset frequency flicker noise of a TMR-based spin-torque vortex oscillator in the regime of large amplitude steady oscillations. We first phenomenologically expand the nonlinear auto-oscillator theory aiming to reveal the properties of this noise. We then present a thorough experimental study of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 56 publications
(116 reference statements)
0
26
1
Order By: Relevance
“…2 ). Note that this description does not apply for frequencies above the relaxation rate frequency ( MHz here) above which the oscillator’s nonlinearities strongly affect the noise PSDs 30 , 32 , 33 .
Figure 2 Measurement of amplitude and phase noise and , respectively, and of frequency spectra corresponding to different measurement durations.
…”
Section: Experimental Noise Psds and Frequency Spectrummentioning
confidence: 99%
See 4 more Smart Citations
“…2 ). Note that this description does not apply for frequencies above the relaxation rate frequency ( MHz here) above which the oscillator’s nonlinearities strongly affect the noise PSDs 30 , 32 , 33 .
Figure 2 Measurement of amplitude and phase noise and , respectively, and of frequency spectra corresponding to different measurement durations.
…”
Section: Experimental Noise Psds and Frequency Spectrummentioning
confidence: 99%
“…Note that in addition to intrinsic origins, external fluctuations of the driving dc current or the applied magnetic field might also play a role. In experiments, the existence of 1/ f noise at low offset frequencies has been reported in the different types of spin torque nano-oscillators based on the dynamics of a uniform magnetic mode 31 , 40 , of the gyrotropic motion of a vortex core 30 , 32 or in nano-contact STNOs 39 . Keller et al 40 have furthermore reported a different influence of the noise sources on the oscillation linewidth and spectral shape, related to the measurement duration.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations